2016
DOI: 10.4236/health.2016.815175
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, Beliefs and Perceived Risk of Acute Coronary Syndrome among Jordanian Patients

Abstract: Background: Acute Coronary Syndrome (ACS)-associated mortality is considered high and still raising, where outcomes can be improved through immediate treatment initiation. Knowledge, attitudes, beliefs and perceived risk are cognitive factors that can affect patient's decision to seek care immediately. Therefore, this study aimed to explore knowledge, attitudes, beliefs, and perceived risk for future ACS event among Jordanian ACS patients. Methods: A descriptive, cross-sectional, correlational design was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
24
12
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(50 citation statements)
references
References 30 publications
(57 reference statements)
8
24
12
5
Order By: Relevance
“…Our results support other authors findings about the lack of knowledge among people who are at high risk for heart attack (O'Brien et al, 2012;Noureddine et al, 2020). However, participants of our study showed lower mean score of knowledge than participants of other studies carried out in Ireland (O'Brien et al, 2012) and in Jordan (Alfasfos et al, 2016), that found, respectively, a mean score of 17.8 (S.D.=3.6) and 16 (S.D.=3.6).…”
Section: Discussionsupporting
confidence: 90%
“…Our results support other authors findings about the lack of knowledge among people who are at high risk for heart attack (O'Brien et al, 2012;Noureddine et al, 2020). However, participants of our study showed lower mean score of knowledge than participants of other studies carried out in Ireland (O'Brien et al, 2012) and in Jordan (Alfasfos et al, 2016), that found, respectively, a mean score of 17.8 (S.D.=3.6) and 16 (S.D.=3.6).…”
Section: Discussionsupporting
confidence: 90%
“…This was not caused by the income but due to the patient's awareness in seeking treatment when ACS attacks occur in which the patient decides to rest, buy non-prescribed medications, and the presumption that the perceived symptoms are common so that particular treatment is not necessary. Alfasfos N, et al, (2016) believed that knowledge, attitudes, and beliefs of respondents are able to influence the Yusniawati, Y.N.P. et al Knowledge and Socioeconomic Status as The Factors of ............................................. .............................................................................................................................................................................. ..............................................................................................................................................................................…”
Section: The Economic Status and Pre-hospital Delay Of Acs Patientsmentioning
confidence: 99%
“…That is, they often show unrealistic optimism bias, which can reduce the accuracy of their risk appraisals and delay their help-seeking behavior ( Weinstein, 1982 ; Blumenthal-Barby and Krieger, 2015 ). Previous research further showed that ACS patients tend to be overly optimistic regarding their risk of cardiovascular events ( Dracup et al, 2008 ; Alfasfos et al, 2016 ; Thakkar et al, 2016 ). The current study raises the possibility that more accurate knowledge of cardiovascular risk factors might contribute to better decision making in patients with ACS by accurately increasing their perceived risk of suffering a cardiac event ( Lefler and Bondy, 2004 ; Darawad et al, 2016 ), reducing the typical unrealistically optimistic perceptions of these patients ( Dracup et al, 2008 ; Alfasfos et al, 2016 ; Thakkar et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%